Brazilian Consensus on Sleep-Focused Speech-Language-Hearing Sciences - 2023 Brazilian Sleep Association - Studart-Pereira, Luciana Moraes; Bianchini, Esther Mandelbaum Gonçalves; Assis, Márcia; Bussi, Marieli Timpani; Corrêa, Camila de Castro; Cunha, Thays Crosara Abrahão; Drager, Luciano Ferreira; Ieto, Vanessa; Lorenzi-Filho, Geraldo; de Luccas, Gabriele Ramos; Brasil, Evelyn Lucien; Sovinski, Silmara Regina Pavani; Zancanella, Edilson; Pires, Gabriel Natan; Consensus Group on Sleep-focused Speech-Language-Hearing Sciences (Sleep Science, 2023)
Introduction This consensus aimed to develop a structured document presenting the role of sleep-focused Speech-Language-Hearing (SPH) Sciences (SPHS). The recommendations were based on the expertise of specialists and on evidence in the literature, aiming to guide the coverage of this area and the consequent improvement in the quality of the professionals' approach.Methods A Delphi method was conducted with 49 SLH pathologists (SLHP), four sleep physicians, one dentist, one physical therapist, and one methodologist. Four Delphi panel rounds were conducted in Google Forms. The items were analyzed based on the panelists' percentage of agreement; consensuses were reached when ⅔ (66.6%) of valid responses were on a same on a same answer (either “agree” or “disagree”).Results Participants voted on 102 items. The mean consensus rate was 89.9% ± 10.9%. The essential topics were the importance of professional training, the SLH diagnosis, and the SLH treatment of sleep disorders. It was verified that all fields of the SLHS are related to the area of sleep; that sleep-focused SLH pathologists (SLHP) are the responsible for assessing, indicating, and conducting specific orofacial myofunctional therapy for sleep-disordered breathing alone or in combination with other treatments; that SLHP are included in interdisciplinary teams in the area of sleep in public and private services.Discussion The Brazilian consensus on sleep-focused SLHS is a landmark in this area. This consensus described the scope of action of sleep-focused SLHP and systematized recommendations being useful as a reference for the professional practice in the area of sleep.
Keywords: sleep; speech; language and hearing sciences; sleep wake disorders; obstructive sleep apnea; consensus; delphi